Biomarkers in cervical cancer screening - Termini, Lara; Villa, Luisa Lina (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Persistent infection with oncogenic human papillomavirus (HPV) is the main risk factor for cervical cancer and its precursor lesions. Cyto logical screening programs using the Pap test have led to a substantial reduction in the incidence of cervical cancer despite its limitation in detecting minor atypias and adenocarcinomas. Therefore, the identification of new biomarkers that allow the monitoring of molecular events associated to tumor progression in histological or citological specimens may improve the detection of lesions with higher risk of progression. HPV DNA detection as a primary screening parameter has been controversially discussed due to its very low predictive value. On the other hand, the development of new technologies for the determination of high risk HPV activity by detecting E6 and E7 transcripts has the potential to more accurately evaluate tumor progression. Moreover, the detailed analysis of HPV oncoproteins and cellular targets will allow the definition of new possible biomarkers. One of the best examples is the up-regulation of the cyclin dependent kinase inhibitor p 1 óink43 expreSSion by E7. Several studies use pl6ink4a overexpression to identify dysplastic cells in histological samples and cytological smears. This review focuses on biomarkers studies and their possible role in screening cervical cancer and precursor lesions.